PENGARUH JUMLAH PENDUDUK, PENDIDIKAN DAN PENGANGGURAN TERHADAP KEMISKINAN DI KOTA PADANG - Syahrial; ANGGRAINi, Reren (Universitas Sumatera Barat, 2021)
This research was conducted to determine the effect of population, education and unemployment on poverty in the city of Padang. The purpose of this study was to test partially and simultaneously the effect of population, education and unemployment on poverty in the city of Padang, using multiple linear regression analysis. The classical assumption test used is the data normality test, autocorrelation test, multicollinearity test and heteroscedasticity test, and the coefficient of determination test. Meanwhile, to test the hypothesis used the F test and t test. The analysis technique used to examine the effect of population, education and unemployment on poverty in Padang City is a regression with the help of SPSS version 16.0. The results showed that the population had a positive and significant effect on poverty as evidenced by a significance value of 0.001. The results showed that education had a negative and significant effect on poverty as evidenced by a significance value of 0.016. The results showed that unemployment had a positive and significant effect on poverty as evidenced by a significance value of 0.042. The results showed that the population, education and unemployment simultaneously had an effect on poverty in the city of Padang, which was indicated by the evidence of a significance value of 0.003. While the coefficient of determination R2 square shows the number 0.237 or 23.7%. So it can be said that 23.7% of the poverty rate is influenced by population, education and unemployment. While the remaining 76.3% is influenced by other variables not examined in this study.